A Encíclica Fratelli Tutti e o diálogo inter-religioso - Sanchez, Wagner Lopes (Revista eclesiástica brasileira, 2021)
This text assumes that interreligious dialogue is one of the keys to reading the Fratelli Tutti encyclic, by Pope Francis. The objectives that guided the construction of the text were: to reflect on the notion of interreligious dialogue present in Fratelli Tutti and to present the different dimensions of interreligious dialogue olso present in Fratelli Tutti. The article shows that interreligious dialogue runs through the encyclic and, at the same time, that the construction of fraternity in today’s times requires that religions put themselves in dialogue.